Overexpression of calcium-binding protein calgranulin B in colonic mucosal diseases - Stulík, J; Kovárová, H; Macela, A; Bures, J; Jandík, P; Langr, F; Otto, A; Thiede, B; Jungblut, P (Clinica chimica acta; international journal of clinical chemistry, 1997)
Subtractive two-dimensional gel electrophoresis (2-DE) has been used for the study of the protein patterns of the normal colonic mucosa and the specimens collected from patients diagnosed for inflammatory bowel disease (IBD), colonic polyps and colorectal cancer. We found a 13 kDa protein that was detected in five of seven adenomas and in 13 of 15 colorectal carcinomas while it was absent or only slightly expressed in normal colonic mucosa. Furthermore, this protein occurred in all specimens collected from patients suffering from IBD and its quantity reflected the increased severity of inflammation. The combination of microsequencing and mass spectrometry led to the identification of the 13 kDa spot as calgranulin B. Our results indicate that the production of calgranulin B is unregulated in inflammatory, preneoplastic and neoplastic lesions of colonic mucosa.
Keywords: kalgranulin B; 2D gelová elektroforéza; Humans; Mass Spectrometry; Calgranulin B; lidé středního věku; nemoci tlustého střeva; Peptide Mapping; Calcium-Binding Proteins; Female; střevní sliznice; Aged; dospělí; Inflammatory Bowel Diseases; Colonic Diseases; senioři; lidé; reprodukovatelnost výsledků; peptidové mapování; Amino Acid Sequence; Adult; idiopatické střevní záněty; Colonic Polyps; ženské pohlaví; kolorektální nádory; Male; Reproducibility of Results; Middle Aged; proteiny vázající vápník; Hydrogen-Ion Concentration; Electrophoresis, Gel, Two-Dimensional; mužské pohlaví; polypy tlustého střeva; koncentrace vodíkových iontů; hmotnostní spektrometrie; Intestinal Mucosa; Colorectal Neoplasms; sekvence aminokyselin